1980
DOI: 10.1042/bj1910193
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of chick-embryo cartilage proteoglycan by selective degradation with chondroitin lyases (chondroitinases) and endo-β-d-galactosidase (keratanase)

Abstract: Digestion of chick-embryo cartilage proteoglycan (type H) with chondroitin AC II lyase or keratanase, in the presence of EDTA, N-ethylmaleimide, phenylmethanesulphonyl fluoride and pepstatin, resulted in the removal of the bulk of the chondroitin sulphate or keratan sulphate chains respectively, without altering the protein portion of the macromolecule. An exhaustive treatment of the proteoglycan with chondroitin AC II lyase followed by digestion with keratanase yielded a core fraction having the enzymically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(102 citation statements)
references
References 34 publications
0
101
0
1
Order By: Relevance
“…Chondroitinase AC-I1 degrades a linkage hexasaccharide into a disaccharide unit and a tetrasaccharide core (Hascall et al, 1972;Oike et al, 1980;Sugahara et al, 1991). HPLC analysis of the chondroitinase AC-I1 digest gave rise to a single radiolabeled component emerging at the position of authentic dHexAa1-3GaI(4S)/31-3-Galpl -4Xyl-ol (Fig.…”
Section: Time (Min)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chondroitinase AC-I1 degrades a linkage hexasaccharide into a disaccharide unit and a tetrasaccharide core (Hascall et al, 1972;Oike et al, 1980;Sugahara et al, 1991). HPLC analysis of the chondroitinase AC-I1 digest gave rise to a single radiolabeled component emerging at the position of authentic dHexAa1-3GaI(4S)/31-3-Galpl -4Xyl-ol (Fig.…”
Section: Time (Min)mentioning
confidence: 99%
“…The purified UTI preparation, which has been demonstrated to consist of four isomers with different electric charges (Yuki et al, 1993), was treated with NaB'H, to release the chondroitin sulfate chain from the peptide and to prepare tracers by radiolabeling Xyl simultaneously at the reducing end of the linkage region. The resultant 'H-labeled chondroitin sulfate was mixed with a carrier prepared by alkaline NaBH, treatment of whale cartilage chondroitin 4-sulfate, isolated by gel filtration on Sephadex G-50 (data not shown) and digested with chondroitinase ABC to obtain the linkage hexasaccharide fraction (Hascall et al, 1972;Oike et al, 1980;Sugahara et al, 1991). Upon gel filtration of the digest on a Sephadex G-50 column two radioactive peaks were observed: a minor peak in the void volume and a major peak in the included volume (data not shown).…”
Section: Isolation Of Linkage Oligosaccharidesmentioning
confidence: 99%
“…Previous studies have shown that proteoglycans extracted from rat glomeruli are eluted from DEAESephacel at >0.45 M NaCl (17 NaDodSO4/PAGE. Electrophoresis of aliquots (=20,000 cpm) of the glomerular extracts, peaks 1 and 2 eluted from DEAE-Sephacel columns, and the immunoprecipitates was carried out on 5-10% gradient slab gels following a modification (19) (20) or with papain (30 pg/ml, 650C, 4 hr).…”
mentioning
confidence: 99%
“…Briefly, NHS-LC-biotin was used for labelling. For the specific degradation of the glycan chains, chondroitin sulphate lyases AC and ABC, heparinase/ heparitinase and keratanase were used in the presence of proteinase inhibitors (Oike et al, 1980;Kato et al, 1985). Electrophoresis of enzyme-treated and non-treated samples was performed as described above.…”
Section: Purification Of Cs/ds Pgmentioning
confidence: 99%